Why should farmers invest in wells when irrigation tanks underperform? the evidence from South Indian tank commands - D Suresh Kumar; K Palanisami (Agricultural Economics Research Review, 2023)
Irrigation tanks are perceived to contribute significantly to irrigation, agricultural production, and environmental sustainability. Realizing the significance of this perception, this paper analyses why farmers should invest in wells when irrigation tanks underperform. If the availability of water in tanks is poor, tanks perform poorly, and water becomes scarce. Farmers respond by increasing the number of private wells. If farmers do not invest, they stand to forgo an income of INR 12,430–12,775 per hectare per year. Therefore, farmers should be helped to construct wells.